Alcohol Consumption Among First-Year Students at Valdosta State University - Finney, Savanna M. (My University, 2020)
The purpose of this research is to examine the amount of alcohol students at Valdosta State University consume in comparison to nationwide statistics. Alcohol consumption has been a constant issue across universities, increasing drop-out rates, unhealthy habits, and other negative outcomes. While approximately 70% of student’s report drinking alcohol, prevalence is highest among first-year students. This research addresses the prominent reasons for excessive alcohol consumption as well as the preventative measures students and the university can take to limit consumption. In order to determine if Valdosta State University students consume as much alcohol as the reported national average, I created a survey and analyzed the results. In my results, I found that a majority of students at Valdosta State University reported as much drinking as other students among national universities, with a prominence in first year.